Presencia de esponjas (Porifera) en el Oligoceno de Costa Rica (Valle Central) - Aguilar A., Teresita (2011)
Sponges belonging te the genera Laocaetis and Farrea were recoverd from an Cligocene section of Miembro Tranquerillas (Pacacua Formatíon, Valle Central). The depositional enviroment is confirmed by the presence of ichnofossils of the genus Entobia BRONN. The studied section is interpreted as a regressive sequence leading froto deep neritic te littoral facies.